DE LA DEMNITATEA UMANĂ LA LIBERTATEA DISCURSULUI ACADEMIC VIA CORECTITUDINEA POLITICĂ (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
From Human Dignity to the Freedom of Academic Discourse via Political CorrectnessHuman dignity can best be defined and understood only in the biblical theology of creation, which states that man is a being created in the image and likeness of God, endowed with conscience, reason and freedom. This is the innate dignity. Freedom is an essential component of dignity, and its main focus is the ethical one, which is the source of the acquired dignity, that is, the prove of innate dignity through the personal acts of the human being. Dignity and freedom are organically linked, and respect for freedom is based on the recognition and respect of dignity. Freedom of expression in the theological discourse in the academic milieu is one of the important forms of manifesting freedom, and political correctness is one of the greatest dangers to this freedom. The freedom of academic discourse is indispensable for an education based on critical discernment and for the training of the skills necessary for a good social life.